Exploring business model innovation for competitive advantage: a lesson from an emerging market. Issue 4 (11th February 2021) - Saqib, Natasha; Satar, Mir Shahid
Abstract : Purpose: Emerging markets are witnessing rapid changes in their economy owing to the ongoing liberalization and globalization. India, as one of the emerging markets in south Asia, is also experiencing a dramatic change in its business ecosystem. This poses huge opportunities to the companies, both start-ups and established ones. In this direction, the business model innovation offers a strategic renewal mechanism. The study aims to explore the practices of an online transport network company (OLA) creating a distinctive place for itself in Indian taxi service sector. Design/methodology/approach: Methodologically, an exploratory case study of an India-based online transport company (OLA) business model innovation is reported. Findings: This paper reveals that OLA has been able to gain competitive advantage in the Indian emerging market by developing an innovative business model with its distinctive features of personalised customer service, asset sharing, usage-based pricing, collaborative ecosystem, agile and adaptive organising and successful expansion strategies. Research limitations/implications: This study adds to current knowledge concerning the theoretical foundations and antecedents of business model innovation as a competitive advantage. The paper is explorative in nature because the analysis is mostly based on literature review. Furthermore, in consideration of the analysis of business model of a single company, further research is required to generalize the results. Practical implications: The understanding of the intricacies of business model innovation can be of great concern to existing and prospective managers and entrepreneurs of emerging markets. Originality/value: The paper discusses the features of innovative business models and how firms can make their business models more relevant to the competitive markets. As such, the study is hopeful to aid practitioners engaged in the pursuit of beating the competition with innovation driven business models.